2018
DOI: 10.2147/ppa.s176651
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of cancer patients and their families toward disclosure of cancer diagnosis in Saudi Arabia: a Middle Eastern population example

Abstract: ObjectivesParticularly in the Middle East, few studies have explored the attitude of cancer patients and their families toward cancer diagnosis disclosure (CDD). This study was conducted to investigate the preference and attitude of a sample of cancer patients and their families in Saudi Arabia toward CDD.MethodsWe constructed a questionnaire based on previous studies. The questionnaire assessed preference and attitude toward CDD. Participants were recruited from the King Abdullah Medical City, which has one o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 27 publications
5
24
0
Order By: Relevance
“…Physicians in China should realize the different attitudes toward CDD between patients and family members . Similar results have been presented in other studies . Moreover, Gan's quantitative study found that physicians were less positive toward cancer diagnosis disclosure (CDD) than patients and family members, consistent with Tang's study results …”
Section: Introductionsupporting
confidence: 84%
See 2 more Smart Citations
“…Physicians in China should realize the different attitudes toward CDD between patients and family members . Similar results have been presented in other studies . Moreover, Gan's quantitative study found that physicians were less positive toward cancer diagnosis disclosure (CDD) than patients and family members, consistent with Tang's study results …”
Section: Introductionsupporting
confidence: 84%
“…Previous studies have demonstrated that there are many benefits of diagnosis disclosure for cancer patients . Despite the low diagnosis disclosure rate in Asian countries, many studies have found that a majority of patients with a terminal illness want to know the truth . Our former study also found that cancer patients' views of diagnosis disclosure were different from those of their family members.…”
Section: Introductionmentioning
confidence: 53%
See 1 more Smart Citation
“…Despite the wishes of the patients to the truth, clinicians still are reluctant to disclose their disease diagnosis in numerous countries. [8][9][10] Prager [11] reported a case in the U.S.A that a 70-year-old Egyptian man who speaks Arabic only presented with bone cancer evidence. When Dr. Prager called to be conducted a biopsy to approve the cancer diagnosis, the family refused to be disclosed any information to the patient.…”
Section: Introductionmentioning
confidence: 99%
“…Still, most of them are reluctant to disclose any information to patients, particularly to patients with malignancy such as breast cancer, prostate cancer, terminally ill patients, and end-stage renal disease. [10,12] Concerning the scarcity in the literature in this region, it would be invaluable to examine the clinicians' attitudes toward truth-telling and related factors. The recent literature reports that clinicians still struggle to find the best way to disclose difficult information without applying harm to patients.…”
Section: Introductionmentioning
confidence: 99%